Analisis Kemampuan Literasi Matematika Siswa Berbasis Self Confidence dalam Pemecahan Masalah Sistem Persamaan Linear Tiga Variabel Kelas X SMA Hang Tuah 3 Mataram - Afra Nisaa Ba’i Atun; I Ketut Sukarma; Yuntawati (Jurnal Kependidikan Ki Hajar Dewantara, 2026)
Mathematical literacy is essential for students to formulate, employ, and interpret mathematics in various contextual problems. This study aimed to describe students’ mathematical literacy skills based on their levels of self-confidence in solving three-variable linear equation system problems among tenth-grade students at SMA Hang Tuah 3 Mataram. The study employed a descriptive qualitative approach. The initial participants were 10 students who completed a self-confidence assessment and a mathematical literacy test. Subsequently, six students were purposively selected as the main subjects, consisting of two students in the high category, two in the moderate category, and two in the low category. Data were collected through a self-confidence questionnaire, a mathematical literacy essay test, and semi-structured interviews. Data analysis involved data reduction, data presentation, and conclusion drawing, while data credibility was examined through technique triangulation. The findings showed that students with high self-confidence tended to fulfil all three indicators of mathematical literacy: formulating problems mathematically, employing mathematical concepts, facts, procedures, and reasoning, and interpreting and evaluating results. Students with moderate self-confidence were able to formulate problems and apply mathematical procedures but were not yet consistent in interpreting results. Students with low self-confidence experienced difficulties in almost all indicators and were unable to explain their solutions independently. Therefore, higher self-confidence tended to be accompanied by better mathematical literacy skills